Bacterial Biofilms - Dincer, Sadik; Sümengen Özdenefe, Melis; Arkut, Afet (IntechOpen, 2020)
This book examines biofilms in nature. Organized into four parts, this book addresses biofilms in wastewater treatment, inhibition of biofilm formation, biofilms and infection, and ecology of biofilms. It is designed for clinicians, researchers, and industry professionals in the fields of microbiology, biotechnology, ecology, and medicine as well as graduate and postgraduate students.